Well prepared yet uncertain: Experiences of the early career transition after affiliation with an interdisciplinary graduate school - Catharina Melander; Charlotte Löfqvist; Maria Haak; Søren E. Smedegaard Bengtsen; Gudrun Edgren; Susanne Iwarsson (PLoS ONE, 2025)
To contribute to the development of effective support for early career researchers during and after doctoral education, the aim of this study was to examine the experiences of the early career transition after affiliation with an interdisciplinary graduate school, using the Swedish National Graduate School on Ageing and Health (SWEAH) as an example. Through qualitative interviews with 18 alumni, the findings reveal that the graduate school had fostered interdisciplinary research skills among early career researchers, and they felt well-prepared for the next career stage. However, they expressed a need for continuous career support and personal guidance while still feeling confident and open-minded. Interdisciplinary graduate schools can play a crucial role in nurturing the next generation of early career researchers, providing them with the skills and identities needed for impactful research and collaboration in a complex, interconnected world. We suggest that academic careers should be understood in an entangled or interlinked way from the very beginning of the academic journey, and introduce a new conceptual coinage of “career ecologies”. This implies that doctoral students and early career researchers should be encouraged, empowered, energized, and invited to activate and make use of their societal voice, influence, and value, right from the early formative doctoral years. Moreover, strategic support is vital to maintain an interdisciplinary spirit and facilitate informed career choices.